The impact of electronic information on the development of the personality of the child. -in present and future- - عبد الرحمن بوحسون (Journal of Architecture and environment of child, 2021)
Although the Internet is a source of educational and social interpersonal communication and an entertaining and entertaining tool for our children. by creating the ability to solve several issues using electronic games and educational programs, it provides them with opportunities to learn, to exchange information and to acquire skills and ideas with friends and colleagues via instant messaging, social networks, etc. However, these people are now facing countless big problems, resulting from the misuse of this network due to the lack of prior censorship by parents on the one hand, and the weak role of educational and security institutions to sensitize and educate the child about the dangers. -This study is to shed light on the role of the family, educational institutions and specialized centers in protecting child from the dangers of the Internet. This study relied on the descriptive approach in presenting pictures of neglect and the size of emotional and physical abuse that a child experiences, whether by his family members or from his teachers in educational institutions and trainers in training centers.